High molecular mass forms of basic fibroblast growth factor are initiated by alternative CUG codons. - Prats, H (1989)
A 6.75-kilobase human hepatoma-derived basic fibroblast growth factor (bFGF) cDNA was cloned and sequenced. An amino-terminal sequence generated from a purified hepatoma bFGF was found to correspond to the nucleotide sequence and to begin 8 amino acids upstream from the putative methionine start codon thought to initiate a 154-amino acid bFGF translation product. This sequence suggests that a form of bFGF of at least 163 amino acids exists. The hepatoma cDNA was transcribed in vitro into RNA; in vitro translation of this RNA generated three forms of bFGF with molecular masses of 18, 21, and 22.5 kDa. By use of in vitro mutagenesis, it was found that the 22.5-kDa bFGF and possibly the 21-kDa form were initiated with CUG start codons. The 18-kDa bFGF was initiated with an AUG codon. By transfecting into COS cells human hepatoma bFGF cDNA and a construct from which the AUG initiator was eliminated, it was found that the higher molecular mass forms of bFGF were as biologically active as the 18-kDa form.